One-Pot Solid-State Reaction Approach to Synthesize Ag-Cu2O/GO Ternary Nanocomposites with Enhanced Visible-Light-Responsive Photocatalytic Activity. (28th March 2017) - Li, Longfeng; Zhang, Jing; Fu, Xianliang; Xiao, Peipei; Zhang, Maolin; Liu, Mingzhu
Abstract : A facile ball milling-assisted solid-state reaction method was developed to synthesize Ag-Cu2 O/graphene oxide (GO) nanocomposites. In the resultant complex heterostructures, Ag nanocrystals were mainly deposited on the surface of Cu2 O, while Ag-Cu2 O composites were anchored onto GO sheets. The resultant Ag-Cu2 O/GO nanocomposites exhibited excellent photocatalytic activity with 90% of methyl orange (MO) dye degradation efficiency after 60 min of visible-light irradiation, which was much higher than that of either Cu2 O or Ag-Cu2 O. This study opens a new avenue to fabricate visible-light-responsive photocatalyst with high performance for environmental pollution purification.